Waste Minimization Factors Among Food Vendors in Manzese Ward, Dar Es Salaam - Geraldine Mwita; David Ndungutse; James G. Wanziima; David R Mutekanga (Adventist University of Africa, 2023)
Background: This study was conducted in the Manzese Ward, Dar-es-Salaam, Tanzania. The objectives were to identify the individual and institutional factors associated with waste minimization among food vendors, determine the level of waste minimization among food vendors, and investigate the association between related factors (individual and institutional factors) and waste minimization among food vendors. Methods: Quantitative data collection strategies were used. The study collected data from 234 participants, selected using a multistage sampling technique. Data were analyzed using descriptive and bivariate analyses, and a multivariate ordinal logistic model was fitted. Results: The results show that most vendors are young (less than 35 years old), have basic education, and have a positive attitude toward waste minimization. The most significant factors for waste minimization among the food vendors' working in Manzese Ward were education level (AOR= 35; 95% CI: 69-0.70; p=029), monthly income (AOR= 49; 95% CI: 20-12; p=118), knowledge level (AOR= 36; 95% CI; 15-85; p<0.003), and attitude (AOR=17; 95% CI: 69-42; p<0.001). These factors are important for reducing waste and maintaining a low waste production by food vendors. Conclusion: The levels of income, knowledge, and attitude of the vendors were identified as being crucial factors in minimizing waste. While provision of equipment for waste segregation, collection and removal, and the provision of sanitary facilities were identified as being important institutional factors contributing towards minimizing of waste.